Kajian Partisipasi Masyarat Dalam Program Pengurangan Risiko Bencana Berbasis Komunitas Di Kota Bitung - Kalangkahan, Patries H; Areros, William A; Sampe, Stefanus (JURNAL ILMIAH SOCIETY, 2016)
Awareness of the importance of Community-Based Disaster Risk Reduction (PRBBK) should be pursued in view of the condition of Indonesia in general and Bitung in particular in geographically and geologically is a disasterprone areas where mainstream disaster events from year to year showed a significant increase. PRBBK program requires the active involvement of communities across the stage of disaster risk reduction. Call for Proposals aims to reduce the vulnerability and increase the capacity of communities to prevent or minimize the potential loss and damage caused by the disaster to life, shelter, livelihoods and the environment. This study aims to assess the community participation in the program of community-based disaster risk reduction in Bitung, this study using research methods kualitatitf.